From oil to natural gas : prospects and challenges for the Trinidad and Tobago economy - Racha, Sandra ([CCMS] [St. Augustine]TT, 2001)
Outlines the importance of the energy sector, the petroleum regime, and possible ways to amend the legislation to realize increased benefits from the natural gas sector.